The role of perceived usefulness and confirmation in influencing student’s satisfaction on online distance learning / Hasnizawati Hashim ... [et al.] - Hashim, Hasnizawati; Mohamad, Siti Aishah; Che Hamzah, Hamnah; A. Halid @ Khalid, Rozieana; Azer, Ilyani (Universiti Teknologi MARA, 2023)
Today's learning opportunities are immense in scale and bolstered by the support of technological advancements. Many universities in Malaysia have contributed to the trend of advancements in education and technology. It was recommended that online distance learning (ODL) and online teaching processes should be used at all levels of education during the COVID-19 pandemic. However, the use of these technological advancements has encountered challenges, which were recognized during the initial application of ODL. Both students and academics faced many obstacles as first-time users of online education. This study explores students’ expectations of ODL based on Expectation-confirmation theory (ECT). A survey was conducted with 579 university students to test the hypotheses of this study. The results of this questionnaire were tested using structural equation modeling (SEM) AMOS mediation analysis. The results showed partial mediating effects between perceived usefulness, confirmation, and satisfaction with online distance learning. Furthermore, it was found that perceived usefulness has a significant influence on student satisfaction with and confirmation of ODL. To ensure that students of higher learning institutions are satisfied with ODL, it is vital for universities and colleges to make these students believe that the application of ODL is useful and can create significant value for them.